Psychological Impact of COVID-19 on Parents of Pediatric Cancer Patients - Guido, Antonella; Marconi, Elisa; Peruzzi, Laura; Dinapoli, Nicola; Tamburrini, Gianpiero; Attinà, Giorgio; Balducci, Mario; Valentini, Vincenzo; Ruggiero, Antonio; Chieffo, Daniela Pia Rosaria (Frontiers in Psychology, 2021)
The changes and general alarm of the current COVID-19 pandemic have amplified the sense of precariousness and vulnerability for family members who, in addition to the emotional trauma of the cancer diagnosis, add the distress and fear of the risks associated with infection. The primary objectives of the present study were to investigate the psychological impact of the COVID-19 pandemic on the parents of pediatric cancer patients, and the level of stress, anxiety, and the child’s quality of life perceived by the parents during the Covid-19 epidemic. The parents of 45 consecutive children with solid and haematological tumors were enrolled. Four questionnaires (Impact of Event Scale-Revised - IES-R ; Perceived Stress Scale - PSS; Spielberger State - Trait Anxiety Inventory - STAI-Y ; Pediatric Quality of Life Inventory - PedsQL) were administered to the parents at the beginning of the pandemic lockdown. 75% of parents exhibited remarkable levels of anxiety, with 60 subjects in state scale and 45 subjects in trait scale having scores that reached and exceeded the STAI-Y cut off. The bivariate matrix of correlation found a significant positive correlation between the IES-R and PSS scores (r = 0.55, P < 0.001). There was a positive correlation between the PSS and PedsQL (emotional needs) scale (P < 0.001) and a negative correlation between IES-R and STAI-Y (P < 0.001). The results confirm that parents of pediatric cancer patients have a high psychological risk for post-traumatic symptoms, high stress levels, and the presence of clinically significant levels of anxiety.